(untitled) (Jurnal Kemanusiaan, 2017)
The financial crisis episode has previously shown fiscal policy importance as a major instrument for national economic stabilization policy, especially through innovation revenue and government expenditure by total or components. Next, the behavior of the directions of government revenue and expenditures within the period, regardless of federal, states or local authorities has also reflected the budget and the fiscal deficit/surplus for the futures. In line with this condition, this study analysis 3 hypotheses which related to the dynamic relation between government revenue and expenditure; taxation-consumption hypothesis, consumption-taxation hypothesis and fiscal adjustments. Overall, the findings show that, most of the state governments are more practicing the fiscal adjustment strategy in the total revenue and expenditure stages, compare with its components.Â Episod krisis kewangan sebelum ini memperlihatkan peri penting dasar fiskal sebagai instrumen utama dalam dasar penstabilan ekonomi negara terutama sekali menerusi inovasi hasil dan belanja kerajaan secara total mahupun komponen. Seterusnya, gelagat serta arah hubungan hasil dan belanja kerajaan tersebut antara tempoh, tidak kira sama ada kerajaan persekutuan, negeri mahupun tempatan, turut mempengaruhi saiz belanjawan dan defisit (surplus) fiskal semasa dan masa hadapan. Rentetan itu, kajian ini menganalisis 3 hipotesis berkaitan kedinamikan hubungan antara hasil dan belanja awam; hipotesis cukai-belanja, belanja-cukai dan penyelarasan fiskal. Secara keseluruhannya, dapatan membuktikan kebanyakan kerajaan negeri lebih mempraktiskan strategi penyelarasan fiskal di peringkat jumlah hasil dan belanja berbanding dengan komponen. Â